2014
DOI: 10.1515/jbcpp-2013-0139
|View full text |Cite
|
Sign up to set email alerts
|

Kolaviron, a biflavonoid fraction from Garcinia kola, protects against isoproterenol-induced injury by mitigating cardiac dysfunction and oxidative stress in rats

Abstract: KV protects against ISO-induced cardiotoxicity in vivo, suggesting its usefulness as a possible chemoprophylactic agent against cardiotoxic drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…Damage to cardiac tissue induced by different β-adrenergic receptor agonist like isoprenaline increases the level of ALT, AST, and ALP enzymes [39]. Myocardial necrosis induced by ISO treatment increases ALT, AST and ALP activities are observed in plasma.…”
Section: Discussionmentioning
confidence: 99%
“…Damage to cardiac tissue induced by different β-adrenergic receptor agonist like isoprenaline increases the level of ALT, AST, and ALP enzymes [39]. Myocardial necrosis induced by ISO treatment increases ALT, AST and ALP activities are observed in plasma.…”
Section: Discussionmentioning
confidence: 99%
“…In the midst of several cardiovascular diseases, ischaemic heart disease is the foremost cause of morbidity and mortality in both industrialized and developing countries and is envisaging, being the key and most common threat to human life by 2020 [1][2][3]. A number of means have been proposed to explicate the myocardial injury and hemodynamic dysfunction during myocardial infarction (MI).…”
Section: Introductionmentioning
confidence: 99%
“…Its antioxidant and anti-inflammatory actions have been employed to protect against many pathological conditions (Adedara and Farombi 2012;Olaleye et al 2000). Its cardio protective (Adaramoye and Lawal 2015) and nephro-protective (Adedara et al 2015) actions have been reported. Gallic acid (Figure 1b) is an endogenous plant phenol that is found in many fruits, teas and wine (Ma et al 2003;Singh et al 2004).…”
Section: R a F Tmentioning
confidence: 99%